A 21st Century Evil: Immunopathology and New Therapies of COVID-19 - Silva, Taylon Felipe; Tomiotto-Pellissier, Fernanda; Sanfelice, Raquel Arruda; Gonçalves, Manoela Daiele; da Silva Bortoleti, Bruna Taciane; Detoni, Mariana Barbosa; Rodrigues, Ana Carolina Jacob; Carloto, Amanda Cristina Machado; Concato, Virgínia Márcia; Siqueira, Elaine da Silva; Costa, Idessania Nazareth; Pavanelli, Wander Rogério; et al. (Frontiers in Immunology, 2020)
Coronavirus Disease 2019 (COVID-19) has been classified as a global threat, affecting millions of people and killing thousands. It is caused by the SARS-CoV-2 virus, which emerged at the end of 2019 in Wuhan, China, quickly spreading worldwide. COVID-19 is a disease with symptoms that range from fever and breathing difficulty to acute respiratory distress and death, critically affecting older patients and people with previous comorbidities. SARS-CoV-2 uses the angiotensin-converting enzyme 2 (ACE2) receptor and mainly spreads through the respiratory tract, which it then uses to reach several organs. The immune system of infected patients has been demonstrated to suffer important alterations, such as lymphopenia, exhausted lymphocytes, excessive amounts of inflammatory monocytes and macrophages, especially in the lungs, and cytokine storms, which may contribute to its severity and difficulty of establishing an effective treatment. Even though no specific treatment is currently available, several studies have been investigating potential therapeutic strategies, including the use of previously approved drugs and immunotherapy. In this context, this review addresses the interaction between SARS-CoV-2 and the patient’s host immune system during infection, in addition to discussing the main immunopathological mechanisms involved in the development of the disease and potential new therapeutic approaches.